1998
DOI: 10.1029/98jd00171
|View full text |Cite
|
Sign up to set email alerts
|

Satellite climatology of African dust transport in the Mediterranean atmosphere

Abstract: These patterns are shown to be related to both cyclogenesis over North Africa and rainfall over the Mediterranean Sea. Indeed, the frequency of dust mobilization over the continent and of dust outbreaks over the sea are strongly related to the climatology of depressions affecting North Africa. Precipitations appear to be an important factor explaining both the seasonal east-west shift in transport location and the south-north gradients of dust concentrations over the Mediterranean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
367
2
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 412 publications
(414 citation statements)
references
References 34 publications
37
367
2
8
Order By: Relevance
“…Milan presented high contributions during spring and summer, Porto during winter and Barcelona during the summer season. These results are in good agreement with Moulin et al (1998), who reported that the annual cycle of African dust transport over the Mediterranean region starts during springtime in the eastern part, while during summer there is maximum transport in the western part. Porto was the only city deviating from this behaviour, suggesting that the studied year may not be representative for this city for assessing seasonal trends, probably due to the low frequency and intensity of dust events.…”
Section: Contribution Of Natural Sources To Pm Concentrations and Excsupporting
confidence: 93%
“…Milan presented high contributions during spring and summer, Porto during winter and Barcelona during the summer season. These results are in good agreement with Moulin et al (1998), who reported that the annual cycle of African dust transport over the Mediterranean region starts during springtime in the eastern part, while during summer there is maximum transport in the western part. Porto was the only city deviating from this behaviour, suggesting that the studied year may not be representative for this city for assessing seasonal trends, probably due to the low frequency and intensity of dust events.…”
Section: Contribution Of Natural Sources To Pm Concentrations and Excsupporting
confidence: 93%
“…When this happens, there is a corresponding induced flow of continental tropical air northwards, transporting dust with it (Dayan et al, 1991). The frequency of dust mobilization over North Africa and of dust intrusions over the Mediterranean Sea are, therefore, strongly related to the climatology of depressions affecting North Africa (Moulin et al, 1998). Katsnelson (1970) attributed dust events over Israel to thermal lows (including Sharav cyclones and Red Sea trough) and mentioned dynamic cold cyclones (Cyprus Lows) as a possible additional factor.…”
Section: Introductionmentioning
confidence: 99%
“…Ganor and Foner (2001) and Moulin et al (1998) showed that the mean annual TSP begins rising as early as January, which is the month in which Cyprus Lows are most frequent (Alpert et al, 1990), while other systems, regarded as producing dust, are less frequent. Both studies also mentioned the fact that dust is removed by precipitations, and therefore the residence time of particles in the atmosphere is much shorter when it rains, as is the case during the Cyprus Lows, and so reduces their signature as a major dust contributor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sahara and its borders constitute the main source of mineral dust, yielding over 50% of the global production. The Saharan dust transport is a significant climatic process (Tanré and Legrand, 1991), primarily westwards, across the Atlantic Ocean (D'Almeida, 1986;Prospero and Lamb, 2003;Petit et al, 2005), but also northwards (Moulin et al, 1998). Mineral dust absorbs and scatters the shortwave and longwave radiations, as well as it emits longwave radiation.…”
Section: Introductionmentioning
confidence: 99%